PENDAMPINGAN REHABILITASI BAGI PECANDU DAN KORBAN PENYALAHGUNAAN NARKOTIKA - Ranu Mahesti (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2018)
This article discusses the importance of rehabilitation for addicts and victims of drug abuse. There are still many Indonesian people who do not know the importance of rehabilitation for addicts, in this article using the method or research literature study. There are 4 types of drugs such as marijuana, methamphetamine, ecstasy, and heroin which are consumed by many addicts who initially only try and then become addicted, if it is dependence it is very difficult to escape from the bondage of drugs without rehabilitation assistance, other than if the effects are allowed to be left very bad and detrimental to many parties. Rehabilitation is a very effective and important way for addicts and victims of drug abuse to stop taking drugs, for example by means of medical or non-medical treatment that leads to better health, long-term recovery, more positive life, life-saving, clean and conscious.